(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2026)
This research aimed to find out how the influence of interjection and expression in improving daily speaking ability at SMAN 3 PANGKEP. The researcher used a quantitative approach to analyze the data. The researcher applied a pre-experimental research design, involved pre-test and post-test. The design involved the students which do the pre-test, got treatment and doing the posttest. The amount of effect of treatment could be accurately known by comparing between pre-test and post-test result. The instrument of this research was speaking test. It aimed to showed data about student proficiency or achievement in speaking English. The result shows that the students mean score in the pre-test was 63.62% while the students mean score in post-test was 82.05%. It was analyzed that there are improvement in students speaking after teaching interjection and expression in the class (18.43%). The paired t-test findings showed that Ha is accepted and H0 is rejected with values of 0.000 and 0.05 (<0.05). It suggests that there is a result improved students speaking by using interjection and expression.